2009
DOI: 10.1111/j.1651-2227.2009.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between peer relationship problems and childhood overweight/obesity

Abstract: The significantly increased prevalence of overweight and obesity among preschool children with peer relationship problems could not be explained by confounding. It seems evident that there is a relevant co-morbidity of peer relationship problems and obesity in pre-school children pointing to the need of interventions focusing on both physical as well as psychosocial health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
15
1
1
Order By: Relevance
“…Similarly, the cooccurrence of obesity and impaired social acceptance has been observed in the US Early Childhood Longitudinal Study when children were 9 to 11-years-old (Jackson & Cunningham, 2015). Interestingly, peer relationship difficulties are apparent even younger, specifically in parental assessments of the well-being of 5-year-old children with obesity (Boneberger, von Kries, Milde-Busch et al, 2009;Griffiths, Dezateux & Hill, 2011). Studies also report more conduct and hyperactivity problems in boys with obesity (Griffiths et al, 2011;Sawyer, MillerLewis, Guy et al, 2006).…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, the cooccurrence of obesity and impaired social acceptance has been observed in the US Early Childhood Longitudinal Study when children were 9 to 11-years-old (Jackson & Cunningham, 2015). Interestingly, peer relationship difficulties are apparent even younger, specifically in parental assessments of the well-being of 5-year-old children with obesity (Boneberger, von Kries, Milde-Busch et al, 2009;Griffiths, Dezateux & Hill, 2011). Studies also report more conduct and hyperactivity problems in boys with obesity (Griffiths et al, 2011;Sawyer, MillerLewis, Guy et al, 2006).…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, overweight children and adolescents are often less liked, and less chosen as friends, and are more rejected, isolated and peripheral to social networks than their normal-weight peers [5,59]. Indeed, large scale community-based studies have shown a greater prevalence of overweight and obesity in preschool children showing problematic relations with their peers in comparison to children with adaptive peer relationships [60]. …”
Section: Reviewmentioning
confidence: 99%
“…9,10 In addition to the (future) health disadvantages (for example, type 2 diabetes, hypertension, and increased cardiovascular risk 11,12 ), children and adults with overweight/obesity are more prone to social and emotional problems. 13 To help prevent such (future) problems, recognition by parents is of critical importance in the early identification of childhood overweight. If overweight is recognised early in life, prevention and treatment strategies are more likely to be successful.…”
Section: Introductionmentioning
confidence: 99%